Rancang Bangun Chatbot Pendidikan Berbasis Web dengan Natural Language Processing untuk Layanan Informasi Publik di SMK Negeri 2 Padang - Rani Nabilla Putri; Elfi Tasrif; Ahmaddul Hadi; Rizkayeni Marta (Universitas Negeri Padang, 2026)
This study addresses the limited efficiency of public information services in vocational schools, which often results in delayed responses and repetitive administrative workload. This research aims to design and develop a web-based educational chatbot using Natural Language Processing (NLP) to improve information accessibility at SMK Negeri 2 Padang. The system was developed using the Waterfall model and implements text preprocessing, TF-IDF vectorization, and cosine similarity for intent recognition. System evaluation was conducted through Black Box Testing and accuracy measurement based on user queries. The results show that the system achieved a 100% success rate in functional testing and 91% accuracy in intent classification, indicating its effectiveness in providing relevant and real-time information. This study contributes by offering a practical, scalable, and user-friendly NLP-based solution to enhance public information services in educational institutions.